Readequação do fluxo de produção e da planta industrial em uma fábrica de embutidos e derivados de carne suína - Dal'Sotto, Jéssica (2016)
Improve the production system is a goal constantly pursued by industries due to competition increasingly fierce between them. The search for improvements becomes a competitive advantage in cost reduction and increase in productivity levels. This work aims to analyze the production flow and to propose improvements in the industrial plant and a readjustment of the production process of a small factory built and derivatives needs to eliminate losses and waste in the process and thereby increase productivity to achieve stand out more at the market in which it operates. The research methodology is based on an exploratory research in the form of a case study. From the evaluation of the production process based on the concepts of planning and control of production and the principles of lean production it was developed a physical model arrangement for the plant. The proposed layout was drawn from the approach of the equipment used in accordance with the order of processes to facilitate the sequence of production and prevent against flows. It was observed, with the final results of the work, that with the adoption of a pull production, we can optimize production times, reducing the intermediate stocks.